(untitled) (HIMALAYA, 2022)
This paper examines the ongoing phenomenon of household nuclearization in the Newar city of Bhaktapur, Nepal. Building upon 15 months of ethnographic research conducted in 2018–19 among middle-class families, I investigate the reasons for household fission and the related kinship transformations. Tracing the interconnected stories of conflict and dispersal of the members of a joint family, I argue that transitions in domestic structures not only represent the consequence of improved economic possibilities but also communicate dramatic social transformations and a redefinition of hierarchies of value and power between family members, which emerge alongside new ideas of family and self. By negotiating domestic spaces and practices, householders redefine a modern dharma to attain a middle class ideal of relatedness. By considering the domestic as the locus of the negotiations between social change and continuity, and by looking at conflict as a dialogical process of cultural revision, this study provides a new perspective on the making of moral modernities in Nepal, ultimately contributing to recent debates in the fields of kinship studies, anthropology of conflict, and moral anthropology.